Peran Mata Pelajaran PKN Dalam Membangun Karakter Anak Sekolah Dasar Pada Kehidupan Sosial - Moch Lucky Winandar; Dinnie Anggraeni Dewi (Departement of Mathematics Education, 2021)
The purpose of this study was to find the role of Pkn subjects in building the character of elementary school children in their social life. And this research is based on researchers' anxiety about the character of the nation's next generation, especially in elementary school children who are starting to deteriorate and deviate from social norms. The number of cases of this deviation is caused by the low character of the nation's successor. There are several factors that cause social deviation, among others, namely; themselves, the role of the family in educating children, and the environment. This shows that the existence of Civics plays an important role in shaping the personality of the nation's future generations. Our lessons are always verbal and only oriented to mastering the content of Civics subjects. The results of observations of daily learning practices show that learning is focused so that students can master the information contained on the topic, then assess the level of mastery of these students. The relationship between teaching materials and everyday life and how to use them to solve problems in life received less attention. Learning seems to be separate from everyday life, so that students do not understand the benefits of what they have learned.